Pengaruh Penggunaan Baja Ringan Hollow Berisi Mortar Sebagai Pengganti Baja Tulangan Terhadap Kuat Lentur Balok - Saputra, Elvis; Rakha Citra Permana Adinata (Universitas Muhammadiyah Surabaya, 2024)
The significant development in Indonesia has led to an increase in the demand for construction materials. One crucial material in building structures is reinforced concrete. Reinforced concrete is a composite material of concrete and steel reinforcement. Steel reinforcement plays a vital role in resisting tensile forces. However, reinforced concrete has a primary weakness, namely, its low tensile strength, which affects the weight of concrete and the overall strength of the building structure. To address this issue, several studies have been conducted to develop lightweight reinforced concrete without compromising its functionality and strength. One innovation introduced is the use of lightweight steel as a replacement for conventional steel reinforcement due to its lower weight. This research aims to investigate the effect of using lightweight steel filled with mortar as a substitute for conventional steel reinforcement on flexural strength. The testing method involves two-point loading and measuring deflection using LVDT on the test specimens. The results of the study show that the comparison between experimental and theoretical nominal moments indicates a minor difference. The experimental nominal moment of lightweight steel reinforced beams increases by 1.84 kNm or 18.91% compared to conventional steel reinforced beams. However, the maximum deflection in lightweight steel reinforced beams is smaller by 23% or 5.9 mm. These results suggest that using lightweight steel can increase the nominal moment while producing smaller deflections.